Pengaruh supervisi akademik, peran serta pada musyawarah guru mata pelajaran dan motivasi guru terhadap kinerja guru SMK negeri di Kabupaten Kulon Progo - Wagiman Wagiman; Supriyoko Supriyoko (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This study aims to determine the influence of: (1) academic supervision, participation in MGMP, and motivation to work together against the performance of SMK teachers in Kulon Progo, (2) the academic supervision against the performance of SMK teachers in Kulon Progo, (3) the participation in Teacher’s Group Discussion (MGMP) against the performance of SMK teachers in Kulon Progo, and (4) work motivation against the performance of SMK teachers in Kulon Progo. This study is an ex-post facto study using quantitative approach. The research was conducted at SMK in Kulon Progo Regency with a total population of 474 vocational high school teachers and samples were taken of 198 teachers by proportional random sampling. The data was collected by a questionnaire. The data processing techniques consist of 1) the classical assumption test which consists of normality test, linearity test and test multicollinearity test, 2) correlation analysis and 3) multiple regression analysis. The results of the study show that: (1) There is a significant positive influence of academic supervision, participation in MGMPs and work motivation on the SMK teacher’s performance in Kulon Progo. (2) There is a significant positive influence of academic supervision on the SMK teacher’s performance in Kulon Progo. (3) There is a significant positive influence of the participation in MGMP on the SMK teacher’s performance in Kulon Progo. (4) There is a significant positive influence of work motivation on the SMK teacher’s performance in Kulon Progo. These facts indicate that the higher or better academic supervision, participation in MGMP and work motivation results in the higher or better teacher’s performance, but otherwise the lower or worse academic supervision, participation in MGMP and work motivation results in the decrease of teacher’s performance produced. In maintaining the good teacher’s performance, the school should facilitate the implementation of academic supervision, active participation in MGMP and the teachers themselves are motivated to perform well.